Diffuse Multicystic Encephalomalacia in a Preterm Baby Due to Homozygous Methylenetetrahydrofolate Reductase 677 C?T Mutation - Aygün, C.; Tanyerı Bayraktar, B.; Bilgici, M.; Baǧci, H.; Küçüködük, Ş. (Sage Publications Inc, 2008)
Methylenetetrahydrofolate reductase catalyzes the formation of 5-methyltetrahydrofolate from 5,10-methylentetrahydrofolate and produces folate for the methylation of homocysteine to methionine. Due to insufficient conversion of homocysteine to methionine, plasma homocysteine levels increase in methylenetetrahydrofolate reductase deficiency. Homocysteine is an amino acid that contains a neurotoxic sulfur molecule and can induce neuronal apoptosis. Methylenetetrahydrofolate reductase deficiency is 1 of the etiological factors that causes neurological symptoms and signs in the newborn and childhood period. Here, we report a premature baby with prenatal onset diffuse multicystic encephalomalacia and cerebellar atrophy due to homozygous methylenetetrahydrofolate reductase mutation. © 2008 Sage Publications.
Keywords: Methylenetetrahydrofolate Reductase Mutation; Multicystic Encephalomalacia